(untitled) (Medico Legal Update, 2021)
This experiment was conducted on 120 unsexed Cobb chicks of one day old for 28 days. Chicks were randomly divided into 4 groups (30 chicks each) and each group consists of two replicates (15 chicks each). All groups was fed using a basal diet, but the first group drunk water from the tap as a control, while the other drunk water with extract of Eruca Sativa leaves (0.25, 0.50 and 0.75ml/Liter) respectively. This study aimed to determine the effect of extraction of Eruca Sativa leaves on broiler performance, some blood parameters and immune response to Newcastle virus. The result showed that the supplementation of the broiler diet with extraction of Eruca sativa especially of levels (0.25 and 0.50ml/L) significantly improve the final body weight (P?0.05). The weight gain also significantly improved (P?0.05) but, there were no significantly changes in the weight of internal organs and blood pictures (WBCs, RBCs, Hb and PCV respectively). The antibody titer against the Newcastle virus found to be significantly increased (P?0.05)